2023
DOI: 10.1111/obr.13548
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, cutoff points, and definition of metabolically healthy/unhealthy obesity in children and adolescents: A scoping review of the literature

Abstract: Diagnosis of metabolically healthy obesity (MHO) and its definition do not have universal criteria in the pediatric age group. Hence, this scoping review aims to identify the components, the cutoff points, and the definition of MHO in children and adolescents. A comprehensive, systematic search was conducted in PubMed, Scopus, EMBASE, and Google Scholar databases. A consensus-based definition of MHO was developed through a Delphi process involving an international panel of 23 experts. This review included a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 107 publications
1
10
1
Order By: Relevance
“…Aligned with previous research, we identified being overweight as a precursor to CKD, underscoring the importance of early intervention 17 . We established that three abnormal indices constitute the optimal threshold for identifying at-risk patients, in line with our scoping review and panel discussion outcomes 15 , 22 .…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Aligned with previous research, we identified being overweight as a precursor to CKD, underscoring the importance of early intervention 17 . We established that three abnormal indices constitute the optimal threshold for identifying at-risk patients, in line with our scoping review and panel discussion outcomes 15 , 22 .…”
Section: Discussionsupporting
confidence: 54%
“…The definition of metabolic health varies across studies and is subject to debate 15 . In this study, we utilized our previously validated definition of metabolic health, which is based on an evidence-based approach combined with expert opinions using the Delphi method 15 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations